2015
DOI: 10.1111/dmcn.12858
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic difficulties in children with mild traumatic brain injury at the subacute stage of recovery

Abstract: EOGElectrooculography ERP Event-related potential LPC Late positivity component mTBI Mild traumatic brain injury AIM Arithmetic difficulties have been reported in children with mild traumatic brain injury (mTBI), but the electrophysiological abnormalities underlying these impairments remain unknown. We therefore used event-related potentials (ERPs) to investigate brain functioning during arithmetic in children in the subacute phase after mTBI.METHOD The participants comprised 16 children with mTBI at the subac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In a cross-sectional study utilizing resting-state EEG, the British Columbia group (Balkan et al, 2015; Virji-Babul et al, 2014) reported increased beta, reduced theta, and reduced delta power across several frontal sources for SRC patients relative to uninjured control athletes, as well as abnormal connectivity metrics. In a study with overlapping samples, the Belgium group (van Beek et al, 2015a) utilized EEG to demonstrate that pmTBI patients exhibited lower amplitude in a late positivity component (posited to reflect attentional failure) during cognitive tasks, but were similar across more basic early sensory components. Finally, Broglio and colleagues (Broglio et al, 2016) prospectively (symptomatic, self-report asymptomatic, return to play, and one-month post asymptomatic) examined an SRC sample and matched uninjured athlete controls for changes in Brain Network Activation, an EEG measure of interconnectedness, during auditory oddball and go/no go tasks.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…In a cross-sectional study utilizing resting-state EEG, the British Columbia group (Balkan et al, 2015; Virji-Babul et al, 2014) reported increased beta, reduced theta, and reduced delta power across several frontal sources for SRC patients relative to uninjured control athletes, as well as abnormal connectivity metrics. In a study with overlapping samples, the Belgium group (van Beek et al, 2015a) utilized EEG to demonstrate that pmTBI patients exhibited lower amplitude in a late positivity component (posited to reflect attentional failure) during cognitive tasks, but were similar across more basic early sensory components. Finally, Broglio and colleagues (Broglio et al, 2016) prospectively (symptomatic, self-report asymptomatic, return to play, and one-month post asymptomatic) examined an SRC sample and matched uninjured athlete controls for changes in Brain Network Activation, an EEG measure of interconnectedness, during auditory oddball and go/no go tasks.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Two hundred and fifty-eight articles were identified from the database searches and reviewed bibliographies, of which 66 were included in the final review (see Supplementary Table 1; Figure 1). Due to the recency of N2 subcomponent classification, the vast majority of included studies referred to the general class of N2 components; only six studied the N2b subcomponent (i.e., Czigler et al, 1996;Lange et al, 1998;Smid et al, 1999;Senkowski and Herrmann, 2002;Czigler and Balázs, 2005;Van Beek et al, 2015). Eight of the included N2 papers specifically investigated concussion (i.e., Broglio et al, 2009;Gosselin et al, 2012;Moore et al, 2014Moore et al, , 2015Moore et al, , 2016Ledwidge and Molfese, 2016;Hudac et al, 2018;Olson et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The N2 group includes several sub-components such as the N2a (more commonly known as the mismatch negativity), which represents pre-attentive stimulus processing in a manner that has been conceptualized in terms of predictive coding (Friston, 2005;Garrido et al, 2009); the N2c, representing stimulus discrimination and response priming; the N2b, discussed in detail below; the N2p, implicated in target detection and global spatial processing; and the N2pc, implicated in visual search (Näätänen and Picton, 1986;Patel and Azzam, 2005;Folstein and Van Petten, 2008;Van Beek et al, 2015). However, due to the lack of consistency in subcomponent classification, components in this group are often referred to as the general "N2" or by their specific latency, such as, "N270" (Connolly et al, 1995;Helenius et al, 1999;Cui et al, 2000;Kong et al, 2000;Wang et al, 2003Wang et al, , 2004Bartholow et al, 2005;Patel and Azzam, 2005;Azizian et al, 2006;Folstein and Van Petten, 2008;Luck, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 Furthermore, concussed subjects who were, on average, over three years post-injury demonstrated decrements in N2 and P3b amplitudes relative to individuals without a history of concussion, 83 in response to a three-stimulus oddball task, although other research has shown no difference. 84 Nevertheless, the P3 component has been repeatedly shown to have chronic amplitude suppression among multi-concussion athletes. [85][86][87][88][89][90][91] However, results have been mixed with previous study of an auditory oddball and Go/No-go tasks not differentiating concussed athletes from controls, [92][93][94] whilst other similar research has shown differences.…”
Section: Eeg and Event-related Potentialsmentioning
confidence: 99%